2020
DOI: 10.1021/acs.jpcc.0c04903
|View full text |Cite
|
Sign up to set email alerts
|

Message Passing Neural Networks for Partial Charge Assignment to Metal–Organic Frameworks

Abstract: Virtual screenings can accelerate and reduce the cost of discovering metal-organic frameworks (MOFs) for their applications in gas storage, separation, and sensing. In molecular simulations of gas adsorption/diffusion in MOFs, the adsorbate-MOF electrostatic interaction is typically modeled by placing partial point charges on the atoms of the MOF. For the virtual screening of large libraries of MOFs, it is critical to develop computationally inexpensive methods to assign atomic partial charges to MOFs that acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 77 publications
1
60
0
Order By: Relevance
“…To date, the most relevant studies focused on training ML models to predict the quantum-chemical properties of MOFs are those of Raza et al 23 and Korolev et al, 24 who independently developed ML models that can predict the partial atomic charges of MOFs in the Computation-Ready, Experimental (CoRE) MOF database. 25,26 Beyond these fundamental studies on partial charge prediction, however, there remains a significant gap in the literature, particularly for the discovery of MOFs with desired electronic structure properties.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…To date, the most relevant studies focused on training ML models to predict the quantum-chemical properties of MOFs are those of Raza et al 23 and Korolev et al, 24 who independently developed ML models that can predict the partial atomic charges of MOFs in the Computation-Ready, Experimental (CoRE) MOF database. 25,26 Beyond these fundamental studies on partial charge prediction, however, there remains a significant gap in the literature, particularly for the discovery of MOFs with desired electronic structure properties.…”
Section: Progress and Potentialmentioning
confidence: 99%
“…The data was small organic molecules and so the model tasks was less focused on macromolecules and conformational effects than this work. Examples of others work using message passing GNNs in chemistry include Raza et al 52 who predicted partial charges of metal organic frameworks, the original message passing paper byGilmer et al 31 which predicted energies of molecules, and St. John et al 53 who predicted bond disassociation energies. There are also first-principles methods for computing NMR chemical shifts, however we do not compare with these since their computational speed and accuracy are not comparable with empirical methods [54][55][56] .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, new charge assignment schemes have been developed based on machine learning (ML) techniques where the ML model is trained on a collection of high-quality DFT-derived charges such as DDEC. 286 , 287 An example of these models is developed by Kancharlapalli et al 286 for MOFs and was shown to be transferable to other porous materials such as zeolites and porous molecular crystals. The ML-based charge assignment schemes are more beneficial for screening of large databases of porous materials where application of DFT-derived partial charges such as REPEAT or DDEC can be computationally very expensive.…”
Section: Multiscale Screening Workflowmentioning
confidence: 99%